The Attention Complex - Rogers, K. author. aut Link
XIII, 246 p. 9 illus.
Keywords: Over the past two decades in the United States, a profound reorientation of human attention has taken shape. This book addresses the recent cultural anxiety about attention as a way of negotiating a crisis of the self that is increasingly managed, mediated, and controlled by technologies.